2019
DOI: 10.3389/fnins.2019.00360
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic Administration of the Histamine H1 Receptor Antagonist/Inverse Agonist Chlorpheniramine to Pregnant Rats Impairs the Development of Nigro-Striatal Dopaminergic Neurons

Abstract: The dopaminergic and histaminergic systems are the first to appear during the development of the nervous system. Through the activation of H 1 receptors (H 1 Rs), histamine increases neurogenesis of the cortical deep layers, while reducing the dopaminergic phenotype (cells immunoreactive to tyrosine hydroxylase, TH + ) in embryo ventral mesencephalon. Although the function of histamine in neuronal differentiation has been studied, the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Several reports have quantified relative tyrosine hydroxylase levels using near-infrared detection as part of a larger study [38][39][40][41][42]. However, the lesions were all produced differently from this report.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Several reports have quantified relative tyrosine hydroxylase levels using near-infrared detection as part of a larger study [38][39][40][41][42]. However, the lesions were all produced differently from this report.…”
Section: Discussionmentioning
confidence: 71%
“…The most common inducer was 6-OHDA injected directly into a region of the nigrostriatal pathway [38][39][40]. One study employed rAAV overexpression of α-synuclein [42] and another report performed a functional block/agonist approach of the histamine H1 receptor [41]. While we provide functional correlation between motor coordination and TH levels, these studies did not report correlative data on physiological or functional outcomes with TH levels.…”
Section: Discussionmentioning
confidence: 90%
“…Reduced methamphetamine-stimulated motor activity in male and female offspring from pregnant rats treated with chlorpheniramine has been reported recently by our group. Interestingly, only males showed reduced speed movement under basal conditions, suggesting sex-specific alterations ( Márquez-Valadez et al, 2019 ), this being the reason why only male animals were included in the present study. However, it will be important to assess females in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that only male pups from chlorpheniramine-treated rats during pregnancy (same dose and time of administration as in this study) showed a decrease in movement speed, in this work, we therefore use only male offspring ( Márquez-Valadez et al, 2019 ).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation